Pengaruh Pendidikan Kesehatan dengan Media Booklet terhadap Pengetahuan Ibu tentang Deteksi Dini Penyakit Pneumonia pada Balita di Kelurahan Bandungrejosari Wilayah Puskesmas Janti Kota Malang - Nurul Atizyah Putri; Herawati Mansur; Sheilla Tania Marcelina (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The incidence of pneumonia has a significant impact on the health of toddlers because the disease can cause death. One of the factors influencing the incidence is the lack of maternal knowledge about early detection of pneumonia. The purpose of this study was to determine the effect of health education with booklet media on mothers' knowledge about early detection of pneumonia toddlers in Bandungrejosari Village, Janti Health Center area, Malang City. This study used preexperimental design with one group pretest-posttest design approach with population of 111 people. The sampling technique used was proportional random sampling, the sample size was 42 respondents. The research instrument used a questionnaire. Data analysis using the Wilcoxon signed rank test. The statistical test results obtained p-value of 0.000 <0,05, which means that there is an effect of health education with booklet media on mothers' knowledge about early detection of pneumonia toddlers in Bandungrejosari Village, Janti Health Center area, Malang City. Based on the results of this study, the provision of health education with booklet media needs to be done so that it can improve mothers' knowledge about early detection of pneumonia toddlers. Future researchers can also use control group as a comparison in this study.